The Relationship between WIF on Job Stress and FIW on Job Stress through Meta-Analysis Studies - Kusuma, Andri; Suyono, Joko (Social work and education, 2020)
The effect of WIF (work interference with family) on the Job Stress and FIW (family interference with work) to the Job stress has produced many findings in empirical research by the previous experts. In this study will re-analyze the effect of WIF on the Job Stress and FIW on the Job Stress with meta-analysis study. This research aimed to know the relationship between WIF on the Job stress and FIW on the job stress through a meta-analysis study based on the 18 proof of empirical study which collected in accordance with the determined criteria. The final goal in this meta-analysis study will be analyze or compare the level of the relationship between WIF on job stress and FIW on job stress. The result of meta-analysis study shows that generally the correlation between WIF to the job stress and also FIW to the job stress found the positive significant. The results of combining the whole study (CI=95%) shows that the relationship FIW on the Job stress including in belongs to the strong category (r=0.54) and for the relationship FIW on the job stress including in belongs to the medium category (r=0.4). Moreover, from the result of analysis of the value of egger’s regression known that there was no publication bias in this meta-analysis study. In the end, the findings in this meta-analysis study concluded that the effect of WIF on job stress has a higher correlation value than the effect of FIW on job stress.